Back‐Projection Imaging of a Tsunami Excitation Area With Ocean‐Bottom Pressure Gauge Array Data. Issue 7 (7th July 2022) - Mizutani, Ayumu; Yomogida, Kiyoshi
Abstract: A back‐projection method has been applied to many earthquakes in seismology due to its simple and low computational cost, and it can estimate complex fault rupture processes without any specific a priori information. In this study, we applied the back‐projection method to the tsunami records observed using an ocean‐bottom pressure gauge array and demonstrated it to be a powerful new tool other than the familiar waveform inversion. The obtained back‐projection image was consistent with the initial tsunami height distributions estimated by previous waveform inversions, and its spatial resolution appeared to be even better. Our result suggests that the fault size of the 2016 Off‐Fukushima earthquake was about half, different from the scaling law of standard earthquakes. The present tsunami back‐projection analysis can also estimate the feature of early tsunami propagations. In addition, the estimated image seems to be reliable even 30 min after the origin time, so the back‐projection analysis will be useful in an early detection of the location and spatial extent of a tsunami source. In the present case, the number of available stations in the analysis was found to be affected by the diffraction of tsunami propagation caused by the refraction by a high velocity zone near the Japan Trench. In other words, the further the source is from the coast, the more stations to be analyzed are available. Since most tsunami‐generating earthquakes occur near the subduction axis or its outer‐rise region, the back‐projection analysis should be effective for source estimation of the majority of tsunami‐generating earthquakes. Plain Language Summary: In seismology, the back‐projection method has been applied to many earthquakes to retrieve their source processes. The operation of the back‐projection analysis consists of a simple stacking of the waveforms shifted with each travel time from a target area. The key points of the back‐projection analysis are therefore the number of stations and accurate travel time estimation. Ocean‐bottom pressure gauge (OBPG) arrays have been recently developed around the world, and the bathymetry or its corresponding tsunami travel time is known much better than the Earth's internal structure. This study is the first attempt to apply the back‐projection method to the tsunami records observed using an OBPG array. We found that the tsunami source area estimated by back‐projection has better resolution than a waveform inversion technique, a popular source estimation method. It was also revealed that the tsunami back‐projection analysis estimates not only the tsunami source but also an early stage of tsunami propagations. Because the back‐projection analysis requires low computational cost, it should be complementary to current tsunami early warning systems. The back‐projection analysis could be an important tool for the tsunami source estimation in the new era of ocean‐bottom array observatories. Key Points: The back‐projection analysis is applied to tsunami records of an ocean‐bottom pressure gauge array associated with the 2016 Off‐Fukushima earthquake Back‐projection images represent not only an excitation area but also detect a part of the feature of early tsunami propagations Our back‐projection result suggests that the fault size of this earthquake was about half of the standard scaling law